To the fauna of Pterophoridae of Venezuela with description of two new species (Lepidoptera: Pterophoridae) - P. Ya. Ustjuzhanin; V. N. Kovtunovich; A. N. Streltzov (SHILAP)
The article describes two new Pterophoridae species from Venezuela: Postplatyptilia lastukhini Ustjuzhanin & Kovtunovich, sp. n. and Postplatyptilia stekolnikovi Ustjuzhanin & Kovtunovich, sp. n. Four species: Stenoptilodes brevipennis (Zeller, 1874), Adaina costarica Gielis, 1992, Adaina desolata Arenberger & Bond, 1995 and Hellinsia devriesi (Landry & Gielis, 1992) are recorded for the fauna of Venezuela for the first time.